Diversification and a Multidisciplinary Approach for Raising Agriculture Production and Attaining Food Security in Smallholder Farming Systems of Sub-Saharan Africa - Munyua, Catherine N; Wagara, Isabel N (Asian Journal of Agriculture and Rural Development, 2015)
Agriculture is the primary economic activity for between 50 and 90 percent of the population in Sub-Saharan African countries. Ninety five percent of the food that is produced in Sub-Saharan Africa is grown through rain-fed agriculture. This implies that the region will suffer most from climate change due to its dependence on rain-fed agriculture. Vulnerability to climate change will be especially significant among the resource poor smallholder farmers in African countries whose livelihoods depend on rain-fed agriculture in marginal areas. African agriculture is characterized by variations in farming systems with about 90% of the farming occurring in integrated systems. In these mixed farming systems, the food security challenge may require an integrated approach to match the existing systems. A rainbow evolution which emphasizes the need for diversified systems may be the best practice in raising agricultural productivity. A multidisciplinary approach based on the theory of embededdness whereby farmers, researchers, extension institutions, and political institutions work together can further raise agriculture production and improve food security. Social networks in communities of farmers provide channels for identifying problems and farmers’ knowledge integrated with that of research and extension can provide sustainable solutions for food production in smallholder farming systems in Africa.